Information processing in medical imaging : 23rd International Conference, IPMI 2013, Asilomar, CA, USA, June 28-July 3, 2013. Proceedings - Joshi, Sarang; Pohl, Kilian M.; Wells, William M.; Zöllei, Lilla; Gee, James C. (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 23rd International Conference on Information Processing in Medical Imaging, IPMI 2013, held in Asilomar in June/July 2013. The 26 full papers and 38 poster papers presented in this volume were carefully reviewed and selected from 199 submissions. The papers are organized in topical sections on connectivity, groupwise registration, neuro segmentation, statistical analysis, dynamic imaging, cortical surface registration, diffusion MRI, functional imaging, torso image analysis, and tract analysis.